NatD promotes lung cancer progression by preventing histone H4 serine phosphorylation to activate Slug expression - Junyi Ju (Nature Portfolio, 2017)
NatD is an acetyltransferase responsible for N-α-terminal acetylation of the histone H4 and H2A and has been linked to cell growth. Here the authors show that NatD-mediated acetylation of histone H4 serine 1 competes with the phosphorylation by CK2α at the same residue thus leading to the upregulation of Slug and tumor progression.